Export-output growth nexus using threshold VAR and VEC models: Empirical evidence from Thailand - Arisara Romyen; Jianxu Liu; Songsak Sriboonchitta (Economies, 2019)
This paper explores the relationship between export, import, and output for Thailand over the period from 1990 to 2017. The threshold vector autoregressive (VAR) and threshold vector error correction (VEC) models were applied. The empirical evidence confirms that the export-led growth hypothesis is valid, implying feedback within the export-output growth nexus. During business cycles, the export-output characteristics in economic cycles can be classified by the two-threshold VAR and VEC models. These relevant variables converge from the long-run equilibrium. As for the thresholds which are correlated, gross domestic product (GDP) vs. export and GDP vs. import exist as a long-run equilibrium relationship, while there does not seem to be a relationship of export vs. import. Furthermore, a five-year forecast was created (the period of 2018-2022). The export-output growth scenarios appear to swing upward continuously throughout the short-term trend. Therefore, policy-makers should highlight countercyclical macroeconomic policies at lower, medium, and upper regimes to strengthen the state of recovery and encourage the state of short recession.
Keywords: F14; O04; 330; non-linear time-series models; export-import pass-through; threshold autoregression; structure break; predictive threshold VAR model